Design and Build a Web-Based Accounting Information System to Optimize Financial Management - Karina Silaen (CV. ADMITECH SOLUTIONS, 2025)
The web-based Accounting Information System (SIA) is an effective solution in improving the efficiency of recording and managing company finances. This research aims to design and develop a web-based SIA using the Rapid Application Development (RAD) method with the Laravel 8 framework. This system is designed to make it easier to record financial transactions and prepare reports automatically and accurately. The result of this study is a system that is able to produce various financial reports, including income statements, balance sheets, cash flows, capital changes, sales reports, and purchase reports. In addition, this system is also equipped with an automatic sales invoice creation feature after a transaction is made. The system was tested using the black box testing method, which showed that all functions were running according to the user's needs. With the implementation of this system, the financial recording process becomes more efficient, accurate, and accessible. This system can help companies make better financial decisions and improve compliance with applicable accounting standards.